Financial System Reforms: Backbone for India's Growth - Leo, John (2007)
The financial sector in India banking, capital markets, insurance, mutual funds etc, has changed since the reforms India under took in nineties. Although many improvements have been effected, this paper will argue that the scope of many of these changes has been relatively narrow and predominantly mechanistic.